The ghost of Taavetti Lukkarinen and the haunting legacy of a 1916 hanging site. (1st October 2016) - Ikäheimo, Janne; Kuvaja, Tiina; Äikäs, Tiina
ABSTRACT: On the fringe of the city centre of Oulu, Finland, stands a peculiar memorial commemorating the last death sentence by hanging in Finland. Here people remembered the ill-fate of Taavetti Lukkarinen, a young man in his early 30s, who was hanged for high treason by Russian officers in 1916. In 2014, archaeological excavation at the hanging tree memorial revealed an interesting group of finds consisting of a deliberately fractured proximal end of a calf tibia with two shards of clear glass and an iron wire inserted into its marrow channel, in addition to a rubber shoe heel pad. These finds can be interpreted as a deposit hidden in the base of the memorial to tie the presumably restless soul to the monument. Examples of this kind of magical thinking with connections to, for example, concealed shoes, are known from different parts of the world. The memorial of Taavetti Lukkarinen may therefore be regarded as an example of a place where both individual people and the society tried to deal with a dark and shameful part of their past.